Accelerated new factory certification using CE methodology - Mohiuddin, A. K. M.; Quick, Wee Hock (2004)
The present paper has demonstrated how Copy EXACTLY! (CE) methodology could be utilized to ramp-up manufacturing capacity within a shortest time possible and concurrently developing fundamental competencies, equivalent to that of any established sites. Everything that might affect the process is to be copied down to the finest detail. The current demands for shifting of manufacturing sites to low cost regions - necessitate the needs for a proven model for a fast and effective start-up and technology transfer. The operational and simulation models have, from time to time - proven to be a forerunner in streamlining business process, reducing product time to market and developing sustainable competitive advantage.